2017
DOI: 10.12691/ajzr-5-2-4
|View full text |Cite
|
Sign up to set email alerts
|

A Quick View on Biology of Near Threatened Peacock Eel (<i>Macrognathus aculeatus</i>) in Khulna Region of Bangladesh

Abstract: The Peacock eel, Macrognathus aculeatus is a near threatened highly valuable small indigenous species in Bangladesh. It is not only toothsome nutritive table fish but also notable aquarium species but still rely on natural stock. Keeping in mind the paucity of information on the biology which is crucial to develop artificial propagation and culture technique of this species, the present research was performed as an attempt to contribute to the information on the taxonomy and other biological aspects of M. acul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Similar observations were perceived by Nabi and Hossain (1996) in the spiny eel, M. aculeatus. Ali et al (2003) reported that the GSI in M. aculeatus ranged from 0.44±0.06 to 14.40±1.48 while Sultana et al (2017) reported the mean GSI of all samples of M. aculeatus as 12.50±1.38.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were perceived by Nabi and Hossain (1996) in the spiny eel, M. aculeatus. Ali et al (2003) reported that the GSI in M. aculeatus ranged from 0.44±0.06 to 14.40±1.48 while Sultana et al (2017) reported the mean GSI of all samples of M. aculeatus as 12.50±1.38.…”
Section: Discussionmentioning
confidence: 99%
“…In a distinct study, substantial variances were also found in DFR and AFR whereas insignificant results were created in remaining meristic characters of Mesopotamian Mastacembelus mastacembelus populations among three locations of the Karakay pool, the Tohma creek and the Tigris waterway (Çakmak and Alp, 2010). Moreover, researchers only assessed meristic counts and they outlined merely descriptive statistics of the Mastacemblidae family namely, (Sultana et al, 2017) in Macrognathus aculeatus, (Plamoottil and Abraham, 2015) in Macrognathusalbus, (Mahmud et al, 2015) and (Narejo et al, 2003) in Mastacembelus armatus. According to Waldman (2005) meristic parameters are worthwhile for delineating stock identification because they specify the initial development and growth of an organism.…”
Section: Resultsmentioning
confidence: 99%
“…Similar research was reported by Plamoottil and Abraham (2014) in Macrognathus albus where the meristic traits were as follows: 26-30 numbers for dorsal fin spines, 14-16 numbers for pectoral fin rays, 11 for caudal fin rays, 3 for anal fin spines. Parallel research was also conducted by Sultana et al (2017) on M. pancalus species resembling 19-39 numbers for dorsal fin spines, 11-18 numbers for caudal fin rays, 29-52 numbers for anal fin rays. Consistent results were also reported by Roberts (1980) on Macrognathus species of meristic characters of number of dorsal fin spines: 14-22 in M. aculeatus, 16-23 in M. aral and 13-19 in M. siamensis.…”
Section: Discussionmentioning
confidence: 99%